Measuring temporal and spatial accuracy in trampolining - Ferger, K.; Hackbarth, M.; Mylo, M. D.; Müller, C.; Zentgraf, K. (Sports Engineering, 2019)
A new measurement system (horizontal displacement, time of flight, synchronicity—HDTS) was investigated regarding the latest changes to the international evaluation rules in trampoline gymnastics. It allows for the real-time measurement of objective criteria, such as flight time and landing position, without affecting the gymnast. The aim of this study was to investigate the temporal and spatial accuracy of a measurement tool via cross-validation. Temporal precision was additionally tested via high-speed video landing and takeoff, while a three-dimensional motion capturing system was incorporated for spatial precision. The Bland-Altman "limit of agreement approach" was used for the assessment of congruence between the measurement systems. The new measurement system presented an average spatial deviation of 3.2 cm and a temporal deviation between - 5.8 and + 6.4 ms for the landing and - 11.3 and + 11.3 ms for the takeoff. Given its temporal and spatial accuracy in determining flight time and landing position as identified through cross-validation, the novel HDTS system proved to be suitable for its use in trampoline competitions.